Chemical treatment for dentin hypersensitivity ‒ Part 1 (Research, Society and Development, 2020)
Objective: To conduct a literature review on the use of chemical substances used in the treatment of dentin hypersensitivity (HD), as well as particularities related to the proposed method. Methodology: A bibliographical search was carried out, through a search in the Medline database (Medical Literature Analysis and Retrievel System Online) seeking studies without restriction of publication date until June 2020, these in English and that portrayed the theme addressed. The search of the database was carried out during the months of April and May 2020. For the search, the following descriptors were used: "dentin sensitivity", "hypersensitivity" and "dental care”. Results: Studies show heterogeneity regarding treatment methods, including also the diversity of substances used. However, there is a favorable direction in the use of the chemical method, combining neural agents and obliterators. Conclusion: Therefore, the chemical method presents good results for the treatment of HD, even with the absence of a clinical protocol for the procedure. When there is the combination of neural agent with obliterator, superior results are observed.